Phenomenology, psychiatric comorbidity and family history in referred preschool children with obsessive-compulsive disorder - Coskun Murat; Zoroglu Salih; Ozturk Mucahit (BMC, 2012)
Abstract Objective The study aimed to investigate phenomenology, psychiatric comorbidity, and family history of obsessive-compulsive disorder (OCD) in a clinical sample of normally developing preschool children with OCD. Method Subjects in this study were recruited from a clinical sample of preschool children (under 72 months of age) who were referred to a university clinic. Subjects with a normal developmental history and significant impairment related to OCD symptoms were included in the study. Children's Yale-Brown Obsessive-Compulsive Scale was used to assess OCD symptoms. Each subject was assessed for comorbid DSM-IV psychiatric disorders using a semi-structured interview. Parents were evaluated for lifetime history of OCD in individual sessions. Results Fifteen boys and ten girls (age range: 28 to 69 months; 54.12±9.08 months) were included. Mean age of onset of OCD was 35.64±13.42 months. All subjects received at least one comorbid diagnosis. The most frequent comorbid disorders were non-OCD anxiety disorders (n=17; 68.0%), attention-deficit hyperactivity disorder (ADHD) (n=15; 60.0%), oppositional defiant disorder (ODD) (n=12; 48.0%), and tic disorders (n=6; 24.0%). Mean number of comorbid disorders was 3.65 and 2.35 for boys and girls, respectively. At least one parent received lifetime OCD diagnosis in 68 percent of the subjects. Conclusions The results indicated that OCD in referred preschool children is more common in males, highly comorbid with other psychiatric disorders, and associated with high rates of family history of OCD. Given the high rates of comorbidity and family history, OCD should be considered in referred preschool children with disruptive behavior disorders and/or with family history of OCD.